СОЦИОКУЛЬТУРНЫЕ АСПЕКТЫ СТИЛИСТИЧЕСКОГО ПРИЁМА ЭПИТЕТА В РАЗНОСИСТЕМНЫХ ЯЗЫКАХ - Рзаева, Р.К.; Жиенбаева, А. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of intercultural communication in teaching English. There have been analyzed the sociocultural aspects of the lexical stylistic device epithet as a means of reflecting the culture of people. On the basis of the comparative analysis of epithets in the works of the English, Russian and Karakalpak writers the author of the article emphasizes the fact, that the sociocultural aspects of the epithet can be discovered only in the context, taking into account the character and interaction of words forming word combinations.
Keywords: intercultural communication; linguosociocultural competency; epithet; trope; sociocultural aspects; mentality; traditions and customs; picture of the world; sociocultural value